Fission yeast cut5 links nuclear chromatin and M phase regulator in the replication checkpoint control. - Saka, Y (1994)
Fission yeast temperature-sensitive cut5 (cell untimely torn) mutants are defective in initiation and/or elongation of DNA replication but allow mitosis and cell division at a restrictive temperature. We show that the cut5 protein (identical to rad4) (i) is an essential component of the replication checkpoint system but not the DNA damage checkpoint, and (ii) negatively regulates the activation of M phase kinase at mitotic entry. Even if the replication checkpoint has been activated previously, cut5 mutations allow mitosis and cell division after shift to 36 degrees C. Transcription of cut5+ is not under the control of the START gene cdc10+. The cut5 protein is enriched in the nucleus, consisting of repeating domains. An essential domain which resembles the proto-oncoprotein Ect2 has a strong negative effect on the entry into mitosis when overexpressed. Expression of the cut5 mutant phenotype requires the function of the M phase regulator genes cdc2+, cdc25+ and cdc13+. The cut5 protein forms a novel, essential link between DNA synthesis and M phase activation in the replication checkpoint control pathway.